Autophagy associated cytotoxicity and cellular uptake mechanisms of bismuth nanoparticles in human kidney cells. (5th June 2017) - Liu, Yongming; Zhuang, Jing; Zhang, Xihui; Yue, Cong; Zhu, Ning; Yang, Liecheng; Wang, Yong; Chen, Tao; Wang, Yangyun; Zhang, Leshuai W.
Highlights: We showed that BiNP can be an excellent CT imaging agent. However, BiNP exhibited more toxicity to kidney cells than other cell types. We are the first to report that bismuth can induce autophagy. The cellular uptake and endocytic pathways in kidney cells were delineated. Bismuth was found to alter DNA methylation related gene expression. Abstract: Bismuth compounds have been used for treatment of bacterial infection, and recently bismuth nanoparticles (BiNP) were synthesized for imaging and diagnostic purpose, while safety concern of bismuth cannot be ignored. Here, we prepared ultrasmall BiNP and showed an enhanced tumor imaging, but BiNP revealed a differentiated cytotoxicity in human embryonic kidney 293 cells (HEK293) compared to other cell types. For the first time, we found that BiNP can induce autophagy, shown as the increase of monodansylcadaverine fluorescence staining and the amount of LC3II that can be inhibited by 3-MA. BiNP were capable of entering cells in a dose and time dependent manner by fluorescence and element detection methods BiNP were found to be localized in the cytoplasm observed by transmission electron microscopy and intracellular bismuth element confirmed by energy dispersive X-ray analysis. Using endocytic inhibitors, BiNP were found to require ATP and endosomal trafficking pathways for their cellular uptake. Internalized BiNP did not co-localize with EEA1, but co-localized with Lysotracker/LAMP1/LAMP2 at late time points, indicating BiNP may be retained in the non-early endosomal vacuoles and late endosomes. With our novel finding of bismuth induced autophagy and endocytic mechanisms, potential approaches may be applied to reduce the toxicity by bismuth.